PERLINDUNGAN HUKUM YANG DILAKUKAN POLRI TERHADAP KORBAN JUAL BELI ONLINE DI WILAYAH POLDA DIY - Sumalugi Sumalugi; Muhammad Hatta; Hartanti Hartanti (Kajian Hasil Penelitian Hukum, 2018)
In law enforcement conducted by Polda DIY related to online buying and selling fraud done by law enforcement effort preventively and law enforcement in repressive. Preventive law enforcement is done by socializing. This implementation is carried out by the entire range of the DIY District Police either from the level of the Resort Police to the Sector Police through appeals to the public to be careful in the use of online media. Repressive enforcement is done by the existence of related public reports that there have been online fraud under the guise of sale and purchase, and when there is a police report to conduct an investigation by referring to the Criminal Procedure Code, while the rule of law to ensnare the perpetrator is based on Law no. 19 of 2016 Amendment to Law no. 11 Year 2008 on Information and Electronic Transactions. Implementation of legal protection by DIY Regional Police against victims of online fraud crime is done by law enforcement which is based on legal protection in penal or non penal, that is law protection done by Polda DIY by optimizing law enforcement process especially related to non penal enforcement by way of undertake preventive efforts against people who have not been victimized to be careful in the use of online media, so that similar fraud events do not happen again. Keywords: Legal Protection, Police, Victim Buy and Sell Online